Working Law: courts, corporations, and symbolic civil rights - Edelman, Lauren B. (Chicago The University of Chicago Press, 2016)
Since the passage of the Civil Rights Act, virtually all companies have antidiscrimination policies in place. Although these policies represent some progress, women and minorities remain underrepresented within the workplace as a whole and even more so when you look at high-level positions. They also tend to be less well paid. How is it that discrimination remains so prevalent in the American workplace despite the widespread adoption of policies designed to prevent it?
Keywords: Civil rights -- United States; Discrimination in employment -- United States; Discrimination in employment -- Law and legislation -- United States